SKA1 regulates actin cytoskeleton remodelling via activating Cdc42 and influences the migration of pancreatic ductal adenocarcinoma cells - Li, Tong (Cell Prolif, 2020)
OBJECTIVES: Spindle and kinetochore–associated protein 1(SKA1), originally identified as a protein essential for proper chromosome segregation, has been recently linked to multiple malignancies. This study aimed to explore the biological, clinical role and molecular mechanism of SKA1 in pancreatic carcinogenesis. MATERIALS AND METHODS: SKA1 expression was detected in 145 pancreatic ductal adenocarcinoma (PDAC) specimens by immunohistochemistry. Biological behaviour assays were used to determine the role of SKA1 in PDAC progression in vitro and in vivo. Using isobaric tags for relative and absolute quantitation (iTRAQ), SKA1’s downstream proteins were examined. Moreover, cytochalasin B and ZCL278 were used to explore the changes of SKA1‐induced signalling and cell morphology, with further confirmation by immunoblotting and immunofluorescence assays. RESULTS: Increased SKA1 expression was significantly correlated with tumour size and cellular differentiation degree in PDAC tissues. Furthermore, elevated levels of SKA1 reflected shorter overall survival (P = .019). As for biological behaviour, SKA1 acted as a tumour promotor in PDAC, overexpression of SKA1 facilitates cell proliferation, migration and invasion in vitro and in vivo. Mechanistically, we demonstrated that SKA1 enhanced pancreatic cancer aggressiveness by inhibiting G2/M arrest and regulating actin cytoskeleton organization via activating Cdc42. CONCLUSIONS: This study revealed novel roles for SKA1 as an important regulator of actin cytoskeleton organization and an oncogene in PDAC cells, which may provide insights into developing novel therapeutics.